Effect of PCSK9 Inhibition by Alirocumab on Lipoprotein Particle Concentrations Determined by Nuclear Magnetic Resonance Spectroscopy. Issue 11 (November 2015) - Koren, Michael J.; Kereiakes, Dean; Pourfarzib, Ray; Winegar, Deborah; Banerjee, Poulabi; Hamon, Sara; Hanotin, Corinne; McKenney, James M.
Abstract : Background: In patients with discordance between low‐density lipoprotein (LDL) cholesterol and LDL particle (LDL‐P) concentrations, cardiovascular risk more closely correlates with LDL−P. Methods and Results: We investigated the effect of alirocumab, a fully human monoclonal antibody to proprotein convertase subtilisin/kexin type 9, on lipoprotein particle concentration and size in hypercholesterolemic patients, using nuclear magnetic resonance spectroscopy. Plasma samples were collected from patients receiving alirocumab 150 mg every 2 weeks (n=26) or placebo (n=31) during a phase II, double‐blind, placebo‐controlled trial in patients (LDL cholesterol ≥100 mg/dL) on a stable atorvastatin dose. In this post hoc analysis, percentage change in concentrations of LDL−P, very‐low‐density lipoprotein particles, and high‐density lipoprotein particles from baseline to week 12 was determined by nuclear magnetic resonance. Alirocumab significantly reduced mean concentrations of total LDL‐P (−63.3% versus −1.0% with placebo) and large (−71.3% versus −21.8%) and small (−54.0% versus +17.8%) LDL‐P subfractions and total very‐low‐density lipoprotein particle concentrations (−36.4% versus +33.4%; all P <0.01). Total high‐density lipoprotein particles increased with alirocumab (+11.2% versus +1.4% with placebo; P <0.01). There were greater increases in large (44.6%) versus medium (17.7%) or small high‐density lipoprotein particles (2.8%) with alirocumab. LDL‐P size remained relatively unchanged in both groups; however, very‐low‐density and high‐density lipoprotein particle sizes increased to a significantly greater extent with alirocumab. Conclusions: Alirocumab significantly reduced LDL‐C and LDL‐P concentrations in hypercholesterolemic patients receiving stable atorvastatin therapy. These findings may be of particular relevance to patients with discordant LDL‐C and LDL‐P concentrations. Clinical Trial Registration: URL:https://clinicaltrials.gov . Unique identifier: NCT01288443.